Determinants of patient satisfaction and its implications on patient loyalty at DOZ clinic and pharmacy in Pangkalpinang City - Nugroho, Fithriawan (Junal Ilmu Manajemen, 2025)
In order to maintain sustainability and a competitive edge, the healthcare sector is a strategic one that significantly depends on patient loyalty and satisfaction. At DOZ Clinic and Pharmacy in Pangkalpinang City, the purpose of this study is to examine how corporate image, service quality, and word-of-mouth (WoM) affect patient satisfaction and how these factors affect patient loyalty. Using the SmartPLS 4.0 tool, the study takes a quantitative approach by employing Structural Equation Modeling based on Partial Least Squares (PLS-SEM). Purposive sampling methods were used to gather data from 96 respondents who are currently enrolled patients. According to the findings, patient satisfaction is positively and significantly impacted by corporate image and word-of-mouth, while service quality has no discernible direct impact. Patient loyalty is significantly impacted by all three independent variables, but word-of-mouth has the biggest impact. Additionally, the association between corporate image and patient loyalty is partially mediated by patient satisfaction. These results emphasize how crucial it is to manage patient-to-patient communication, service quality, and institutional image in order to foster enduring loyalty in the healthcare industry.